Keamanan Data melalui Enkripsi Studi Kasus dengan Algoritma RSA - Salsabila Putri Hati Siregar; Nur Aisyah Pandia; Putri Ramadani; Ibnu Rusydi (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2026)
Data security is a critical aspect in the digital era due to the increasing exchange of sensitive information through electronic media. One widely used approach to protect data confidentiality is cryptography, particularly asymmetric encryption algorithms. This study aims to analyze the implementation of the Rivest–Shamir–Adleman (RSA) algorithm as a data security mechanism through an encryption and decryption process. The research method used is an experimental approach by implementing the RSA algorithm in a text-based data security simulation. The stages include key generation, encryption, and decryption processes, followed by analysis of the correctness and effectiveness of the algorithm in maintaining data confidentiality. The results show that the RSA algorithm is capable of converting plaintext into unreadable ciphertext and successfully restoring it to its original form through the decryption process using the correct private key. This confirms that RSA provides a high level of security based on the difficulty of factoring large prime numbers. The implication of this study is that the RSA algorithm can be effectively applied to secure sensitive data transmission in information systems, especially in environments requiring strong authentication and confidentiality.